Morphologic analysis of the 1st and 2nd tarsometatarsal joint articular surfaces - Melissa R. Requist; Tim Rolvien; Alexej Barg; Amy L. Lenz (Scientific Reports, 2023)
Abstract Tarsometatarsal joint arthrodesis is used to treat a variety of injuries and deformities in the midfoot. However, the surgical technique has not been optimized, in part due to limited knowledge of morphologic features and variation in the related joints. Previous research has relied primarily on dissection-based anatomical analysis, but quantitative imaging may allow for a more sophisticated description of this complex. Here, we used quantitative micro-CT imaging to examine dimensions, distance maps, and curvature of the four articular surfaces in the first and second tarsometatarsal joints. Image segmentation, articular surface identification, and anatomic coordinate systems were all done with semi or fully automatic methods, and distance and size measurements were all taken utilizing these anatomic planes. Surface curvature was studied using Gaussian curvature and a newly defined measure of curvature similarity on the whole joint and on four subregions of each surface. These data show larger articular surfaces on the cuneiforms, rather than metatarsals, and define the generally tall and narrow articular surfaces seen in these joints. Curvature analysis shows minimally curved opposing convex surfaces. Our results are valuable for furthering knowledge of surgical anatomy in this poorly understood region of the foot.